GIS-LIKE ENVIRONMENTS AND HBIM INTEGRATION FOR ANCIENT VILLAGES MANAGEMENT AND DISSEMINATION - V. Barrile; E. Genovese (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2024)
Over the past two decades, we have witnessed significant progress in the digitization of artistic and cultural heritage, which was initially aimed at conservation and analysis but has since expanded its scope to emphasize the dissemination and knowledge of artworks and sites of historical, archaeological, and architectural interest. For ancient villages management and dissemination, there are numerous existing tools, among these Building Information Model (BIM), Geographic Information System (GIS), virtual reality, augmented reality, and mixed reality apps and online platforms. These design and analysis systems have, however, interoperability and integration problems. In attempt to solve these problems, in this context, the research activity involves the creation of a 3D model, and HBIM of Precacore complex starting from the points cloud obtained by images acquired by DJI mini 3 pro. The procedure for importing the 3D HBIM model in a GIS environment using Autodesk Infraworks software will be described, followed by the creation of the Virtual/Augmented/Mixed reality app using the Unity 3D platform and Microsoft Hololens for the purpose of attempting to solve the problems relating the different data format deriving from the use of the commercial software from a virtual point of view. Finally, the methodology for the creation of a hybrid and experimental system will be proposed that, by exploiting the Cesium ion platform, allows the possible (although not complete) effective integration of the multi-scale information contained in both software used for the modeling HBIM and GIS.